Use of Antithrombotic Therapy and Long-Term Clinical Outcome Among Patients Surviving Intracerebral Hemorrhage. Issue 7 (July 2016) - Ottosen, Tobias Pilgaard; Grijota, Miriam; Hansen, Morten Lock; Brandes, Axel; Damgaard, Dorte; Husted, Steen Elkjær; Johnsen, Søren Paaske
Abstract : Background and Purpose—: The effectiveness and safety of antithrombotic therapy (AT) among patients with a history of intracerebral hemorrhage remain uncertain. We therefore determined the prevalence of indication for AT among patients hospitalized with first-time intracerebral hemorrhage and examined the impact of subsequent AT use on the long-term clinical outcome. Methods—: We performed a population-based cohort study using nationwide Danish medical registries. Patients with risk of thromboembolism surviving the first 30 days after hospitalization because of intracerebral hemorrhage were identified and followed up. We estimated the hazard ratio of all-cause death, thromboembolic events, or major bleeding according to use of AT. Results—: We identified 6369 patients between 2005 and 2013. Among these patients, 2978 (47%) had indication for AT, and during the follow-up, (median: 2.3 year) 1281 (43%) died, 497 (17%) had a thromboembolic event, and 536 (18%) had major bleeding. Postdischarge use of oral anticoagulation therapy among patients with indication for oral anticoagulation therapy was associated with a significant lower risk of death (adjusted hazard ratio, 0.59; 95% confidence interval, 0.43–0.82) and thromboembolic events (adjusted hazard ratio 0.58; 95% confidence interval, 0.35–0.97) and no increased risk of major bleeding (adjusted hazard ratio 0.65; 95% confidence interval, 0.41–1.02). In contrast, use of platelet inhibitors among patients with indication for platelet inhibitors was not related to statistically significantly improved clinical outcome. Conclusions—: Approximately 1 of 2 patients surviving intracerebral hemorrhage had a high risk of thromboembolism. Postdischarge use of oral anticoagulation therapy was associated with a lower risk of all-cause mortality and thromboembolic events and no increased risk of major bleeding. Abstract : Supplemental Digital Content is available in the text.